Aplicação de revestimentos de quitosana incorporados de óleo essencial de cymbopogon citratus (D. C.) Stapf. Para o controle de antracnose em frutos - Oliveira, Priscila Dinah Lima (2017)
Several disorders can affect the fruits, especially in the postharvest phase, highlighting a cause of anthracnose by fungi belonging to the genus Colletotrichum. The control of anthracnose has been done basically through the use of synthetic fungicides, which have negative impacts on the environment and the health of consumers. In this sense, other methods have been studied as alternatives to these compounds, including essential oils (EOs), such as essential oil of Cymbopogon citratus (D. C.) Stapf (CCEO), and polymers with ability to form edible coatings, such as chitosan (CHI), which are recognized as antifungal properties. The aim of this study was to evaluate the effectiveness of the application of the coating based on CHI and CCEO in the control of anthracnose in guava cultivar (cv.) Paluma, manga cv. Tommy Atkins and papaya cv. Papaya caused by C. asianum, C. fructicola, C. tropicale, C. siamense and C. karstii. Analysis were performed to identify the constituents of the CCEO; evaluation of the in vitro effects of CHI and OECC alone and in combination on radial mycelial growth and the type of interaction established by these combination substances (additive, synergistic or antagonistic); and assays to verify the effect of coatings based on CHI and CCEO on the development of anthracnose caused by different species of Colletotrichum tested in guava, mango and papaya stored at 25 ° C for 12 days. CCEO (0.15, 0.3, 0.6, 1.25, 2.5 L/mL) inhibited fungal mycelial growth (3 - 100%) of all Colletotrichum strains tested in laboratory medium (Potato Dextrose Agar). Different combinations of CHI (2.5, 5 or 7.5 mg / mL) and CCEO (0.15, 0.3, 0.6 or 1.25 μL / mL) had a fungicidal effect (100% inhibition) against all fungal strains. A total of 30 constituents (≥0.1% of the total mass) were identified in the CCEO. Geranial (51.39%) and neral (29.29%) were found as major constituents of the CCEO. CCEO (2.5, 1.5, 0.6, 0.3 or 0.15 μL / mL) inhibited fungal mycelial growth (3 - 100%) of all Colletotrichum strains tested in laboratory medium (Potato Dextrose Agar). Different combinations of CHI (7.5, 5 or 2.5 mg / mL) and CCEO (1.25, 0.6, 0.3 or 0.15 μL / mL) showed a fungicidal effect (100% inhibition). Application of CHI (5 mg / mL) and CCEO (0.6, 0.3 or 0.15 μL / mL) coatings resulted in reduced development of typical anthracnose lesions in guava (33 - 100%), mango (63 - 100%) and papaya (28 - 100%) artificially contaminated with any of the Colletotrichum species tested during the entire storage period. The CHI 5 mg / mL + CCEO 0.6 μL / mL combination was the most expressive. The percent reduction in the diameter of the anthracnose lesion (PRAL%) in the fruits coated with the combinations of CHI and CCEO was similar to or greater than that observed when the fruits were treated with the synthetic thiophanate-methyl fungicides and difenoconazole. These results indicate that the application of coatings contains synergistic combinations of CHI and CCEO may be considered an alternative technology for the control of anthracnose in fruits, especially in guava cv. Paluma, mango cv. Tommy Atkins and papaya cv. Papaya.